The Notary's Responsibility for Defective Legal Sale and Purchase Deeds (A Review of the Decision of the District Court of Wonogiri Number 13/PDT.G/2021/PN WNG) - Hutagalung, Lorraine Anggi Taruli; Rahaditya, R. (Eduvest - Journal of Universal Studies, 2023)
This research discusses the authority of the Land Deed Official (Pejabat Pembuat Akta Tanah or PPAT) to issue authentic deeds, specifically Sale and Purchase Deeds (Akta Jual Beli or AJB), in the process of transferring land rights through sale and purchase, where authentic deeds hold full probative force. The case under consideration involves the misuse of PPAT authority in the execution of their duties. PPAT, in carrying out their responsibilities in creating authentic deeds, must adhere to the principles of caution and precision. The responsibility of the PPAT for a legally defective Sale and Purchase Deed in the Decision of the District Court of Wonogiri Number 13/PDT.G/2021/PN Wng. is discussed. In the judgment, it is explained that the PPAT violated the law due to the failure to meet the legal requirements of the agreement as per Article 1320 of the Indonesian Civil Code. This research is normative juridical, utilizing a qualitative data analysis method. To examine legal issues, primary legal sources, secondary legal sources, and tertiary legal sources are used, and these sources are subsequently analyzed using descriptive analytical techniques.